2020
DOI: 10.4085/1062-6050-0575.19
|View full text |Cite|
|
Sign up to set email alerts
|

Collegiate Athletes' Concussion Awareness, Understanding, and -Reporting Behaviors in Different Countries With Varying Concussion Publicity

Abstract: Context Concussions are a global public health concern, and education on the importance of self-reporting may not reach all athletes to the same degree around the world. Objective To determine if differences were present in the concussion awareness, understanding, and -reporting behaviors of collegiate athletes' in 3 countries with varied degrees of concussion publicity. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
0
27
2
Order By: Relevance
“…Regardless of the history of concussion and symptom reporting, athletes felt negative about reporting concussion symptoms because they would not be allowed to start playing or practicing when they thought they were ready; the mean Likert-score here was 4.1/5.0 (82.0%). Several previous studies have shown that the common reason for non-disclosure of concussion symptoms was that "they did not want to leave the game/practice (Kerr et al, 2016b;Beidler et al, 2018Beidler et al, , 2021". In other words, continuing in a match or practice is a high priority for athletes.…”
Section: Attitudes Toward Reporting Concussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regardless of the history of concussion and symptom reporting, athletes felt negative about reporting concussion symptoms because they would not be allowed to start playing or practicing when they thought they were ready; the mean Likert-score here was 4.1/5.0 (82.0%). Several previous studies have shown that the common reason for non-disclosure of concussion symptoms was that "they did not want to leave the game/practice (Kerr et al, 2016b;Beidler et al, 2018Beidler et al, , 2021". In other words, continuing in a match or practice is a high priority for athletes.…”
Section: Attitudes Toward Reporting Concussionmentioning
confidence: 99%
“…In other words, continuing in a match or practice is a high priority for athletes. In addition, many athletes did not report concussion symptoms because they did not know it was a concussion and/or did not think it was serious enough (Kerr et al, 2016b;Beidler et al, 2018Beidler et al, , 2021. These findings suggest that education about signs and symptoms might not be sufficient on its own to improve reporting behavior.…”
Section: Attitudes Toward Reporting Concussionmentioning
confidence: 99%
See 3 more Smart Citations